Pengaruh Likuiditas, Leverage, Profitabilitas, dan Ukuran Perusahaan terhadap Kebijakan Dividen pada Perusahaan Manufaktur di BEI - Ubrin Yulianwar; Gendro Wiyono; Alfiatul Maulida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The research conducted aims to see the effect of liquidity, leverage, profitability, and company size on dividend policy in manufacturing companies on the IDX with a search period between 2017-2019 with the method used is the purposive sampling method and the tests carried out are f and t tests. with the aim of knowing the relationship with each other. The results of the research conducted indicate that the Liquidity coefficient (CR) has a regression coefficient of 0.004 which is positive. Effect of Leverage (DER) on Dividend Per Share (DPS) Policy. The significance level is 0.372, which means it is greater than the significance level a = 0.05. This shows that the leverage variable does not have a significant effect. The profitability variable (ROI) has a regression coefficient of 0.288 where the regression coefficient is positive. The Effect of Firm Size (SIZE) on Dividend Per Share (DPS) Policy. The significance level is 0.304, which means it is greater than the significance level a = 0.05. This shows that the size of the company does not have a significant effect. Keywords: liquidity, leverage, profitability, firm size